Determination of Regression Functions for the Charging and Discharging Processes of Valve Regulated Lead-Acid Batteries - Vukic, Vladimir Đ. (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
Abstract: Following the deep discharge of the valve-regulated lead-acid batteries of the type AGM SVT 300, using the ten-hour-discharge current, charging of the batteries with the variable current was performed. In accordance with the obtained results, exponential and polynomial functions for approximation of the specified processes were analyzed. The main evaluation instrument for a quality of the implemented approximations was the adjusted coefficient of determination, R^2. It was perceived that the battery discharge process may be successfully approximated both with exponential and the second order polynomial function. On all the analyzed occasions values of the adjusted coefficient of determination were greater than 0.995. Charging process of the deeply discharged battery was successfully approximated with the exponential function, with the measured values of the adjusted coefficient of determination being nearly 0.95. Beside the high measured values of the adjusted coefficient of determination, polynomial approximations of the second and third order did not provide satisfactory results regarding the interpolation of the battery charging characteristics. A possibility for a practical implementation of the procured regression functions in uninterruptible power supply systems was described.